Preparing Educators to Leverage Technology for Oral Language Development: Teacher Training for Technology Integration - Milimo Mundia (Journal of Indigenous Culture, Tourism, and Language, 2026)
Purpose: This study aimed to examine how specific training programs enable English language teachers to effectively integrate technology to develop students’ oral language abilities. It identifies the key professional competencies, training approaches, and institutional support systems for successful technology integration in speaking and listening development. Research Methodology: A mixed-methods approach was used, including both quantitative and qualitative methods. The sample included 180 English teachers and trainers from Namangan, Uzbekistan, supplemented with international best practices. Data were collected through surveys, observations, and interviews and analyzed using statistical and thematic methods. Results: Key findings include: (a) practice-based professional development (PD) with hands-on workshops, digital tool microteaching, and coaching yields the best results; (b) teachers' digital proficiency and pedagogical understanding of oral activities influence technology adoption in classrooms; and (c) infrastructure and institutional policy are crucial for successful technology implementation. Conclusions: Effective teacher-training programs should focus on practice-based PD and coaching. Teachers' digital competence and pedagogical methods for oral activities are vital. Institutional infrastructure and supportive policies are necessary for successful technology integration into classrooms. An evidence-based teacher-training system is essential for scaling technology-based oral language instruction. Limitations: The study is limited by its small sample size, short-term outcomes, and regional focus, which limit its generalizability. Contributions: This study provides evidence for effective teacher training programs and offers recommendations for scalable technology-based oral language instruction.